2021
DOI: 10.1177/13684302211016961
|View full text |Cite
|
Sign up to set email alerts
|

Outgroup threat and the emergence of cohesive groups: A cross-cultural examination

Abstract: Evolutionary models and empirical evidence suggest that outgroup threat is one of the strongest factors inducing group cohesion; however, little is known about the process of forming such cohesive groups. We investigated how outgroup threat galvanizes individuals to affiliate with others to form engaged units that are willing to act on behalf of their in-group. A total of 864 participants from six countries were randomly assigned to an outgroup threat, environmental threat, or no-threat condition. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Additionally, research on outgroup threat and the emergence of cohesive groups through subtle behavioral cues offers insights into the social dynamics that can be modeled in rodents. Understanding how these cues influence group behavior and stress responses can inform addiction research [114].…”
Section: Study Microaggressions Through Subtle Threat Cuesmentioning
confidence: 99%
“…Additionally, research on outgroup threat and the emergence of cohesive groups through subtle behavioral cues offers insights into the social dynamics that can be modeled in rodents. Understanding how these cues influence group behavior and stress responses can inform addiction research [114].…”
Section: Study Microaggressions Through Subtle Threat Cuesmentioning
confidence: 99%
“…Evolutionary models suggest that threat creates a common enemy and elicits group cohesion for threat resolution (Brooks et al, 2021). An emergency can drive human motivation for engagement in cooperation and increase public-good contributions to the ingroup (Francois et al, 2018; Lang et al, 2022; Majolo and Maréchal, 2017). Johnson et al (2015) found that threat is associated with a greater level of emergency management planning collaboration.…”
Section: Social Capital As An Instrument To Tackle the Crisismentioning
confidence: 99%
“…Broad ethnographic, historical (Gelfand, 2019;Gelfand et al, 2011) and experimental evidence (Lang et al, 2021) suggests that threats increase the need for affiliation, cooperative behaviour and in-group fairness. It has been argued that intergroup conflict was a constant evolutionary force that shaped human social psychology towards evolved dispositions that increased parochialism when under out-group threat (Bowles, 2008(Bowles, , 2009Whitehouse et al, 2017).…”
Section: Out-group Threat and The Ethos Of Dissentmentioning
confidence: 99%